Teachers' and guidance counselors' perceptions of the guidance program in the Division of Guimaras - Grecia, Enrique P. 1949- (1980)
This study was conducted to determine the perceptions of teachers and guidance counselors of the guidance program of the Division of Guimaras. The study involved 208 teachers and 50 guidance counselors, randomly selected from the 558 teachers and 119 guidance counselors of the Division, respectively. A questionnaire was developed by the researcher and was content-validated by a jury of five. The guidance program in the Division of Guimaras was found to be inadequately implemented by both teachers and guidance counselors. It was concluded that the guidance program is an accepted program of the division, but is inadequately supported and implemented.
Appendices: leaves 97-161
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: Personnel service in education -- Philippines -- Guimaras Island